1981
DOI: 10.1056/nejm198112103052403
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acquired Immunodeficiency in Male Homosexuals, Manifested by Chronic Perianal Ulcerative Herpes Simplex Lesions

Abstract: Four homosexual men presented with gradually enlarging perianal ulcers, from which herpes simplex virus was cultured. Each patient had a prolonged course characterized by eight loss, fever, and evidence of infection by other opportunistic microorganisms including cytomegalovirus, Pneumocystis carinii, and Candida albicans. Three patients died; Kaposi's sarcoma developed in the fourth. All were found to have depressed cell-mediated immunity, as evidenced by skin anergy, lymphopenia, and poor or absent responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
117
0
8

Year Published

1984
1984
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,135 publications
(126 citation statements)
references
References 21 publications
1
117
0
8
Order By: Relevance
“…The acquired immunodeficiency syndrome (AIDS) presents a severe unexplained immune deficiency that involves reduction in the number ofhelper T lymphocytes (OKT4) (1)(2)(3). The disease is usually accompanied by multiple opportunistic infections and/or malignancies, the latter predominantly of the Kaposi sarcoma type (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The acquired immunodeficiency syndrome (AIDS) presents a severe unexplained immune deficiency that involves reduction in the number ofhelper T lymphocytes (OKT4) (1)(2)(3). The disease is usually accompanied by multiple opportunistic infections and/or malignancies, the latter predominantly of the Kaposi sarcoma type (4).…”
mentioning
confidence: 99%
“…The disease is usually accompanied by multiple opportunistic infections and/or malignancies, the latter predominantly of the Kaposi sarcoma type (4). AIDS-related complex (ARC) encompasses milder forms and sometimes prodromal states of the disease, and it is characterized by other clinical manifestations, most frequently unexplained chronic lymphadenopathy or leukopenia involving helper T lymphocytes (1)(2)(3)(4). Recent serologic and viral isolation studies have shown that the development of AIDS or ARC is due to infection with the human retrovirus, human T-cell lymphotropic virus type III (HTLV-III) (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Acquired immunodeficiency syndrome (AIDS) is associated with a retrovirus [lymphoadenopathy-associated virus (1), human T-cell leukemia virus type III (HTLV-III) (2), AIDSrelated virus (3)] that is cytotoxic for the OKT4+ subset (helper subset) of T cells and that apparently can result in a devastating series of opportunistic infections that are frequently fatal (4)(5)(6). The AIDS retrovirus can be transmitted in blood products such as donated whole blood (7) and factor VIII concentrates (8), so that methods to determine previous exposure of potential donors to the retrovirus are essential.…”
mentioning
confidence: 99%
“…In vitro, HTLV-I and HTLV-II infection transforms these T4 cells (14)(15)(16)(17), whereas infection with HTLV-III (or LAV) produces cytopathic effects and cell death (9,12). In vivo, the malignant cells from patients with ATLL and the patient with T-cell hairy cell leukemia are T4 cells (8,15,18,19), and in patients with fully developed AIDS the number of circulating T4 cells is profoundly reduced (20,21). However, it is not clear whether HTLV replicates primarily or exclusively in the T4 lymphocyte population.…”
mentioning
confidence: 99%